Spermatozoal Fractalkine Signaling Pathway Is Upregulated in Subclinical Varicocele Patients with Normal Seminogram and Low-Level Leucospermia - Salwa M. Abo El-khair; Mohammad A. Gaballah; Mamdouh M. Abdel-Gawad; Sherif Refaat M. Ismail; Ayman Z. Elsamanoudy (Advances in Urology)
Background. Fractalkine is produced in seminal plasma in small amounts and correlates with sperm motility. Purpose. To investigate the possible effect of low-level leucospermia on spermatozoa oxidative stress and sDNA fragmentation in patients with subclinical varicocele and apparently normal seminogram, and also to study the role of spermatozoal fractalkine and its receptor (CX3CR1) gene expression as a marker of spermatozoa inflammatory response. Methods. This study included 80 patients with subclinical varicocele (45 fertile and 35 infertile) and 45 age-matched fertile volunteers. In semen samples, fractalkine and CX3CR1 gene expression were investigated by qRT-PCR. Moreover, seminal plasma malondialdehyde (MDA) and total antioxidant capacity (TAC) were measured. Results. There are significant decrease in semen quality and significant increase in seminal leucocytes count in subclinical varicocele. Our results show a significant increase in MDA and TAC levels, DNA fragmentation, and expression levels of fractalkine and its receptor (CX3CR1) in subclinical varicocele groups. Conclusion. Subclinical varicocele induces seminal and spermatozoal subclinical inflammatory response in the form of low-level leucospermia and increased mRNA expression of the fractalkine signaling pathway, leading to increased spermatozoal ROS production, oxidative stress, and DNA fragmentation. These could cooperate in the pathogenesis of delayed fertility in males with subclinical varicocele.